Mapping Integration Mechanisms and Enablers in Omnichannel and Multichannel Retailing: Bibliometric Evidence - Primanola Perdananti; Ratih Hurriyati; Puspo Dewi Dirgantari; Timilehin Olasoji Olubiyi (Indonesian Scientific Publication, 2026)
Integration-oriented omnichannel and multichannel retailing has gained prominence as retailers seek to deliver seamless customer journeys while coordinating store operations, inventory, and fulfillment across channels. Yet, prior studies remain dispersed across customer-centric research that emphasizes perceived integration quality and experiential outcomes and operations-centric work that models coordination decisions under cost and profitability objectives. This study aims to map the thematic structure and coverage gaps of integration-oriented omnichannel and multichannel retailing using bibliometric analysis focused on integration mechanisms and enabling conditions. Using Scopus-indexed English journal articles and reviews, records were screened to retain B2C retail or retail-like studies in which channel integration is the primary analytical focus. Performance analysis was conducted with Biblioshiny (bibliometrix) to produce standard, reproducible performance indicators, whereas science mapping employed VOSviewer to construct and cluster author keyword co-occurrence networks that reveal the domain’s thematic structure, using a lean cleaning strategy (minimal thesaurus and lean stopwords). The results reveal two partially connected regimes bridged most consistently by customer-facing operational mechanisms around omnichannel retailing, including BOPIS/click-and-collect, pickups, ship-from-store, and emerging cross-channel returns. In contrast, systems-level digital backbone and governance-related constructs appear weakly consolidated, indicating limited thematic development of integration enablers. The findings suggest that advancing the field requires moving beyond broad omnichannel labels toward auditable, mechanism-linked integration designs that connect customer outcomes, operational execution, and enabling capabilities.